A Near‐Infrared Dye That Undergoes Multiple Interconversions through Acid–Base Equilibrium and Reversible Redox Processes. (9th May 2017) - Asai, Kengo; Fukazawa, Aiko; Yamaguchi, Shigehiro
Abstract: A near‐infrared (NIR) polymethine dye (1 ), consisting of a cyclohepta[1, 2‐ b ;4, 3‐ b′ ]dithiophene and two phenol moieties, was synthesized. This dye exhibited pH‐responsive changes in its photophysical properties due to a two‐step acid–base equilibrium that produced a protonated cation (1H + ) and an anion (1 − ). While1H + showed an intense fluorescence in the red region of the visible spectrum, 1 − exhibited a strong absorption in the NIR region. The tropylium ion character in1H + induces high p K a1 and p K a2 values for1 . Moreover, a stable radical (1 . ) was prepared, which showed a NIR absorption band with a maximum at circa 1600 nm. The cyclic voltammogram of1 . revealed a two‐step reversible redox process that produced1 − and the cation1 +, which is different from1H + . These redox processes accompany drastic electrochromic changes in the vis–NIR region. Overall, 1 is susceptible to multiple interconversions between five forms, due to the multifaceted character of the cycloheptadithiophene skeleton.